The Epidemiology and Clinical Manifestations of Dysexecutive Syndrome in Parkinson’s Disease - Ceravolo, Roberto; Pagni, Cristina; Tognoni, Gloria; Bonuccelli, Ubaldo (Frontiers in Neurology, 2012)
This mini-review summarizes the evidence of the cognitive and behavioral features of dysexecutive syndrome in Parkinson’s disease (PD). Deficits in response inhibition, set-shifting, mental flexibility, and strategy have been frequently described from the earliest stages of PD, although there are inconsistencies in study findings due to the complexity of the executive function (EF) construct and methodological limitations. Behavioral disorders of PD, e.g., apathy, distractibility, perseverative behavior, and impulse-control disorders, may be viewed as the other side of dysexecutive syndrome. Despite the interrelationship between the cognitive and behavioral domains, some reports reveal that the two syndromes may be dissociated, suggesting that both aspects must be clinically assessed. EFs are widely associated with the prefrontal areas, although dysexecutive syndrome may be observed in patients with damage to other brain regions. EFs drive numerous abilities essential to daily life, such as prospective remembering and language comprehension, which may be impaired in PD subjects. Considering the impact of dysexecutive syndrome on independence and quality of life, early detection of executive impairment is crucial in the management of PD.